2003
DOI: 10.1002/ddr.10188
|View full text |Cite
|
Sign up to set email alerts
|

Adenosine A3 receptors in the rat hippocampus: Lack of interaction with A1 receptors

Abstract: Adenosine acts as a neuromodulator in the hippocampus essentially through activation of inhibitory A 1 receptors. Using single-cell PCR analysis, we found that CA1 pyramidal cells coexpress A 1 receptor mRNA together with that of another adenosine receptor, the A 3 receptor. As occurs for the A 1 receptor, Western blot analysis indicated that the A 3 receptor is also located in hippocampal nerve terminals. However, activation of A 3 receptors with its purportedly selective agonist Cl-IBMECA (0.1-10 mM) failed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…The activation of A3 receptors by adenosine may also desensitize A1 receptors. A3 receptors are present in rat hippocampal nerve terminal membranes (Lopes et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…The activation of A3 receptors by adenosine may also desensitize A1 receptors. A3 receptors are present in rat hippocampal nerve terminal membranes (Lopes et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…59 Instead, in cortical neurons the A 3 AR activation depresses the signal transmission by inhibiting glutamate release independently from A 1 AR providing neuroprotection. 60,61 Interestingly, some contrasting evidence was reported in astroglia, where nanomolar concentrations of the A 3 AR agonist Cl-IB-MECA provided neuroprotection, while micromolar doses induced apoptosis. 62 It seems that astrocyte destruction is aimed at isolating the damaged areas [63][64][65][66] through the stimulation of caspase 3.…”
Section: A Role Of a 3 Ar In Normal And Damaged Brainmentioning
confidence: 99%
“…Finally, compound 57 showed comparable good profile at the hA 3 AR. In the Elzein's series (58)(59)(60)(61)(62), compounds 59, 61, and 62 displayed high binding affinities (K i hA 3 AR$2.0 nM) and selectivities for the hA 3 AR (hA 1 /hA 3 Z900 and hA 2A /hA 3 Z1,200). In this specific series, it was found that at the N 6 -position of the 2-pyrazolyl adenosine analog, the methyl group was optimal for high hA 3 AR binding affinity and selectivity.…”
Section: Substitution At the Adenine Moietymentioning
confidence: 99%
“…Regarding adenosine A 3 receptors, their level of expression in the brain is low [26], albeit they are located in hippocampal nerve terminals [27]. Nevertheless, one study showed that an adenosine A 3 receptor agonist, Cl-IBMECA (100 nM), could increase LTP at Schaffer fibers/CA1 pyramid synapses in vitro, an effect prevented by a selective A 3 receptor antagonist, MRS 1191 (10 µM).…”
Section: Effects Of Adenosine a 1 Receptor Antagonists And Adenosine mentioning
confidence: 99%